Strategic Positioning in the Chinese Market: A Case Study of Walmart - Ke Feng; Denis Paleev (Communications of International Proceedings, 2022)
Chinese economy every year grows. Despite economic crisis, Chinese economy remains attractive for investment, which makes new and existing companies compete for market share. Such a company as Walmart, Inc. carries out its activities on the territory of China since 1996, its unit Walmart China cjmprises more than 300 sales outlets and the company develops online commerce. The relevance of the topic is due to potential of the companies development on the Chinese market. The aim of the paper is to analyze a possille strategy of the Walmart, Inc. company on the Chinese market. As a methodological base, SWOT and PEST analyzes were used, as well as SPACE-matrix to obtain more practical recommendations. The works of both English-speaking and Chinese authors engaged in the study of the Chinese economy and its connection with the world market were actively involved. In the end, the author gives a list of recommendations for the further strategic development of the company.
Keywords: strategy; new markets; market capture; strategic planning; Walmart China; business prospects; company opportunities.